Can the changing nature of jobs account for national trends in job satisfaction? - Francis Green; Nicholas Tsitsianis (University of Kent, Department of Economics, 2004)
We investigate whether trends in job satisfaction, which arguably signal trends in worker well-being, can be explained by changes in the quality of jobs. There were falls in job satisfaction in both Britain and Germany. Elsewhere job satisfaction has been either stable or declining very slowly. In many countries, the series of data on job satisfaction is too short to be confident that any secular trend has taken place. We estimate fixed effects models of the determinants of job satisfaction, in order to attempt to account statistically for trends in job satisfaction in Britain and in Germany. We find that: The intensification of work effort and declining task discretion account for the fall in job satisfaction in Britain. The modest rise in participation in organisational decision-making only mitigated the downward pressure on job satisfaction to a small extent. Contrary to what might be expected from popular commentary, changing job insecurity does not explain the fall in job satisfaction in either country. In Germany there was a modest fall in the proportion of people working the number of hours that they wanted to. However, while working too few or too many hours is a significant source of job dissatisfaction, the changes were too small to have made much of an impact on job satisfaction in Germany. In Britain, the increasing proportions of over-educated workers have had a small downward impact on job satisfaction. The decline in job satisfaction between 1984 and 1998 in Germany remains a puzzle.
Keywords: J2; J3; J28; C21; C23; 330; Job satisfaction; unemployment expectations; labour market; labour mobility; panel data; Germany; Britain; Arbeitszufriedenheit; Arbeitsmobilität; Arbeitsmarktflexibilität; Vergleich; Großbritannien; Deutschland